The amorphization of metal nanoparticles in graphitic shells under laser pulses. (May 2020) - Sun, Jun; Sinha, Shyam Kanta; Khammari, Amir; Picher, Matthieu; Terrones, Mauricio; Banhart, Florian
Abstract: It is shown that graphitic shells encapsulating metal nanoparticles facilitate the amorphization of metals and stabilize the amorphous phase against recrystallization. In an in-situ electron microscopy experiment, where the objects are exposed to laser pulses during their observation, the amorphization of iron and cobalt nanocrystals in graphitic shells is demonstrated. The infrared nanosecond pulses lead to fast melting of the metal which then dissolves carbon atoms from the shell. Fast cooling of the liquid solution after the pulse results in the solidification of an amorphous metal-carbon phase. The amorphous phase is metastable and can be recrystallized by repeated laser pulses or slow thermal annealing. The recrystallization needs heterogeneous nucleation but is unfavorable at the metal-graphite interface and so stabilizes the amorphous phase against recrystallization. The analysis of the experiments explains the formation mechanisms of an amorphous metal-carbon phase as a metastable solution of carbon in a transition metal and shows how that the encapsulation by a graphitic shell can be a route towards the stabilization of otherwise unfavorable amorphous metal or metal-carbon phases. Graphical abstract: Image 1